Convergence of ABC and ABM Principles – Guarantee of a Performant Management - Sorinel CĂPUŞNEANU; Dana-Maria MARTINESCU (Theoretical and Applied Economics, 2010)
This article describes the principles of Activity-Based Costing and Activity-Based Management. By its analysis it has been deduced that ABC method becomes the main instrument of providing information for the ABM method. So, the ABM method becomes an important instrument for obtaining performances in business and the warranty for a performing management.